CONTRIBUTION OF COMMUNITY BASED ORGANIZATIONS IN ENHANCING RURAL COMMUNITY DEVELOPMENT: INSIGHTS FROM OSUN STATE, NIGERIA - Famakinwa, Michael; Babawale, Damilola Leah; Sadiku, Olusola Sidikat; Fadodun, Abiodun Rukayat; Ibrahim Adekunle, Adebayo; Onasoga, Deborah Pelumi (Applied Studies in Agribusiness and Commerce, 2025)
This study examined the contribution of community-based organizations (CBOs) to rural community development in Osun State, Nigeria. Specifically, it described the characteristics of CBOs, identified their goals, types, and development projects, determined their contributions to rural development, and identified challenges limiting their performance. A multi-stage sampling procedure was employed to select 48 registered CBOs across the state, with 180 respondents. Data were collected through structured interview schedules and analyzed using descriptive statistics, while Pearson Product Moment Correlation (PPMC) was applied to test the study hypotheses. Results indicated that the mean years of formation of CBOs was 21.3 ± 9.5 years, majority had written constitution with a mean membership strength of 40±12 members. Primary goal of CBOs was economic empowerment of members (85.4%), The most prevalent CBOs included landlord associations and social groups. Most CBOs initiated erection of security gate at community entrance (75%) and provision of vigilante (70/8%). Provision of security for community and government property (mean = 2.83) and implementing of developmental projects (mean = 2.70) were s the most prominent contribution of CBOs. The major constraints affecting CBO performance were lack of funds (mean = 1.85) and lack of government support (mean = 1.51). Statistically significant relationships were observed between contribution and leadership tenure (r = -0.276, p ≤ 0.01), operational constitution (r = -0.406, p ≤ 0.01), and membership size (r = 0.299, p ≤ 0.05). The study concluded that despite the fact that CBOs contributed meaningfully to rural development, their potential remains constrained by limited institutional and community support. It is recommended that government should recognize and institutionalize the role of CBOs in rural development